Pengaruh Pembiayaan Mudharabah dan Istishna Terhadap Profitabilitas Bank Umum Syariah Periode 2021-2024 - Febriyanti, Ika; Amijaya, Rachmania Nurul Fitri; Maulani, Afrida (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to determine the effect of mudharabah financing and istishna on profitability using the Return on Asset (ROA) ratio of Islamic commercial banks in Indonesia in the period October 2021-June 2024. The study uses quantitative data analysis techniques with multiple regression methods using Eviews12 software. The data used is a type of secondary data obtained from the official OJK website. The data analysis technique uses descriptive analysis, classical assumption tests, multiple linear regression and hypothesis testing. The results of this study indicate that partially the mudharabah variable and the Istishna variable have an effect on profitability. Simultaneously, the mudharabh and istishna variables have an effect on profitability, which is 48.7%. While the remaining 51.3% is explained by other variables outside the two independent variables studied.